Brahminism - V T Rajshekar; RAJSHEKAR (V T) (New Delhi Gyan Publishing House, 2015)
Brahminism which is the scientific name for Hinduism, is not a religion like Christianity, Islam or Budhism. It is an ideology. Those who subscribe to this ideology may be born Brahmins or even non- Brahmins like Kshatiryas, Vaishyas and some top landed shudra castes. In fact, some non $1 (BBrahmin castes are better practitioners of Brahminism than the Brahmins who are its prime promoters. Even some Untouchables and Tribals are getting brahminised. But whether they be Brahmins or non -Brahmins, nobody has gained by holding on to this anti -human ideology except that it helps the strong to exploit the weak.s
Keywords: Brahmanism; India; Caste